Ion Chromatographic Determination of Free Cyanide in Different Classes of Bottled Natural Mineral Water Consumed in Turkey - Cengiz, Mehmet Fatih; Durak, M. Zeki; Nilufer, Sukriye; Bilgin, Ayse Kevser (TAYLOR & FRANCIS INC, 2015)
An ion chromatographic method for the quantitative determination of free cyanide in bottled natural mineral waters were measured in terms of selectivity, linearity, the limit of detection, limit of quantification, repeatability, precision, and accuracy. Chromatographic separation of free cyanide ions was accomplished with an anion-exchange column and detected by pulsed amperometric detection with a silver working electrode. The method was found to be selective, linear (r(2) = 0.999) at a concentration range of 0.5 to 134 mu g L-1, precise, and accurate. Recovery values of free cyanide in all classes of natural mineral water varied from 65.9 +/- 1.6 to 95.2 +/- 0.7 at different spiking levels (5-70 mu g L-1). Parameters (total dissolved solids, mineral interferences, and added sodium hydroxide) affecting the recovery values were studied in this project. The limit of detection and limit of quantification were found to be 0.295 and 0.983 mu g L-1, respectively. The proposed method was applied to 27 different brands of commercially available bottled natural mineral water products sold in Turkish markets. These natural mineral waters were classified as: (i) very low mineral concentration, (ii) low mineral concentration, (iii) intermediate mineral concentration, and (iv) high mineral concentration based on their total dissolved solids contents according to European Union Directive (Directive 80/777/EEC). Levels of free cyanide residues in the samples ranged from > limit of detection to 6.12 mu g L-1. The highest average concentration of free cyanide residues was found in the class of high mineral concentration waters. However, the determined free cyanide values in all of the tested natural mineral water samples were found to be within the limits of European Union legislation.
Keywords: Bottled natural mineral water; Free cyanide; Ion chromatography; Method validation; Quality; PULSED AMPEROMETRIC DETECTION; SINGLE-DROP MICROEXTRACTION; SILVER ELECTRODE; THIOCYANATE; SULFIDE; Food Science & Technology